Estruturas de mercado de fatores e governança na cadeia produtiva do leite: um estudo de caso do município de Ajuricaba - RS - Breitenbach, Raquel (2008)
Concerning the milk production chain, the structure of monopsony in the market of factors has its domain for many years in the State of Rio Grande do Sul. It has been verified in the last years especially from 2004 is a significant increase in the amount of the milk processing companies in the North of the State of RS, concentrating in regions which has strong milk basins. This fact provokes, consequently, the increase of the concurrence between these companies in relation of the acquisition of its main raw material, the in-natura milk. It was identified a region in the town of Ajuricaba-RS, where historically just one company was responsible for the purchase of the raw material and, since 2004, several companies dispute for the milk produced in that location. The objective of the present research was to investigate, in this region, how the concurrence in the acquisition of the raw material interfered in the transactions between processing company and farmer and in its domain in the milk productive chain. Based on the characteristics and in the nature of the investigation, this study is embedded in a research of a qualitative sort and utilizes the Study of Case method. The review of the literature (to compose the theoretical corpus of the study), the observation and the interview (to accomplish the field work) was used as research devices. The concurrence in that location brought changes in the people involved. These changes raised the costs of transaction, characterized by a higher frequency in the transactions, caused by the increase of the uncertainty, of the opportunism and consequently making a more limited rationale. Yet the structure of domain adopted in the concurrence ambient, compared to the one adopted in the monopsony ambient, remain it hybrid, but became closer to a via market management. It is asserted second the observation that the price has became the single factor of decision by the dealer to sell its production to one or another purchaser. With any other management strategies previously adopted by the companies not influencing his decision like, for instance, the payment for the milk quality, financings and technical support. Combined to that, a need for a monthly renegotiation of the product occurred, with the elaboration of informal short-term contracts.